Co-Incidence of Diabetic Ketoacidosis and Thyroid Crisis at Klungkung Regional General Hospital - Wedanta Mahadewi, I Gusti Agung; Putri Purnama Dewi, Ni Made (Green Publisher, 2024)
Diabetic ketoacidosis (DKA) is a complication of diabetes mellitus characterized by uncontrolled of hyperglycemia, metabolic acidosis and increased ketone concentrations in the body. Thyroid crisis is one of the acute and life-threatening complications of hyperthyroidism where the symptoms involve multi-organ systems. The coincidence of DKA with Thyroid Crisis is rare and the pathophysiology of this coincidence is not well known and is still widely debated. Early recognizing and managing both emergencies will improve the success of patient management. In these case report there is a coincident of DKA and thyroid crisis at Klungkung Regional General Hospital. Case Report: KS, female, 57 years old came to the emergency room of RSUD Klungkung with the main complaint of nausea and vomiting accompanied by shortness of breath, cough with yellow phlegm and fever since 5 days ago. Other complaints were weakness, dizziness, and palpitations. The patient has a history of DM since 3 years ago and is routinely treated using basal and prandial insulin. Thyroid disease was known since 6 months ago and routinely took Tiamazol, but since 5 days ago the patient stopped the medication because he felt weak and ate little because of complaints of nausea and vomiting with concerns that blood sugar was falling. On examination of vital signs the patient appeared very ill, consciousness E3V4M6 appeared agitated. Blood pressure 130/80 mmHg, pulse 102x/min. Respiratory rate 28x/min seemed fast and deep breaths, axillary temperature 390C with oxygen saturation 89% room temperature and 98% with oxygen 4 liters per minute nasal cannul. On auscultation of the lungs, coarse rhonki sound in the right and left paracardial confirms the clinical pneumonia. On laboratory examination, hyperglycemia was found, with blood glucose (BS) 456mg/dL, urinalysis results obtained ketones +3 and glucose +3. The results of blood gas and electrolyte analysis showed metabolic acidosis at pH 7.17, PCO2 19.0mmHg, HCO3- 7.0 mmol/L, BE (B) -22mmol/L and Potassium 5.4mmol/L. FT4 was 29.87 pmol/L and TSH <0.10 uIU/mL with a Burch Wartofsky score of 55 supporting the diagnosis of thyroid crisis. The patient was admitted to the intensive care unit with the management of hydration to overcome fluid and electrolyte balance disorders, blood glucose regulation with rapid insulin drip, administration of thyroid hormone activity antagonists and management of pneumonia with adequate antibiotics. Discussion: DKA and thyroid crisis are two separate events and their co-occurrence is rare. Both are life-threatening conditions that if not treated promptly will lead to death. The pathophysiology of the coincidence of DKA and thyroid crisis is unknown and debated. One theory states that thyrotoxicosis will change carbohydrate metabolism and increase insulin resistance by increasing glycogen breakdown in the liver, while uncontrolled glucose production will increase metabolic damage. Management of this coincidence requires tight regulation of the patient's glucose levels as the administration of corticosteroids in the management of thyroid crisis runs the risk of increasing glucose levels and thus aggravating the patient's DKA condition. Conclusion: A case of DKA coincidence with thyroid crisis triggered by pneumonia in a 57-year-old woman at RSUD Klungkung has been reported. By correcting fluid and electrolyte balance disturbances, tight blood glucose regulation, administration of antithyroid and corticosteroids at optimal doses and handling pneumonia with adequate antibiotics gave good results to the patient.